2021
DOI: 10.1097/qad.0000000000003067
|View full text |Cite
|
Sign up to set email alerts
|

Trends in HIV prevalence by self-report among MSM diagnosed and reported with gonorrhea in six United States jurisdictions from 2010 to 2019

Abstract: Background: HIV co-infection among persons diagnosed with gonorrhea is not well characterized. Trends in HIV prevalence among persons diagnosed with gonorrhea may have significant implications for HIV prevention interventions, especially for MSM. MSM are increasingly and disproportionately represented among incident gonorrhea cases reported in a multistate sentinel surveillance network. Using data from this network, we estimated HIV prevalence among MSM by self-report and explored trends in co-infection by key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…However, ascertaining the relative roles that exposure and biologic risks play in this disproportionality is challenging. Sexual behavior that confers risk for HIV acquisition also increases risk for acquiring other sexually transmitted infections (STIs) leading to a similar disproportionate overrepresentation of ** https://www.cdc.gov/poxvirus/monkeypox/clinicians/smallpox-vaccine.html † † https://www.cdc.gov/poxvirus/monkeypox/clinicians/monitoring.html § § https://www.cdc.gov/poxvirus/monkeypox/considerations-for-monkeypoxvaccination.html MSM with HIV among STI cases (20); risk for monkeypox through sexual contact is likely similarly increased. Although it is possible that poorly controlled HIV would increase risk for monkeypox after exposure, evidence from other diseases suggests that persons with HIV infection who are receiving ART and have robust CD4 counts are not at increased risk for most infections, including opportunistic infections, and therefore might not be at increased risk for monkeypox after exposure.…”
Section: Monkeypox In Persons With Hiv Infectionmentioning
confidence: 99%
“…However, ascertaining the relative roles that exposure and biologic risks play in this disproportionality is challenging. Sexual behavior that confers risk for HIV acquisition also increases risk for acquiring other sexually transmitted infections (STIs) leading to a similar disproportionate overrepresentation of ** https://www.cdc.gov/poxvirus/monkeypox/clinicians/smallpox-vaccine.html † † https://www.cdc.gov/poxvirus/monkeypox/clinicians/monitoring.html § § https://www.cdc.gov/poxvirus/monkeypox/considerations-for-monkeypoxvaccination.html MSM with HIV among STI cases (20); risk for monkeypox through sexual contact is likely similarly increased. Although it is possible that poorly controlled HIV would increase risk for monkeypox after exposure, evidence from other diseases suggests that persons with HIV infection who are receiving ART and have robust CD4 counts are not at increased risk for most infections, including opportunistic infections, and therefore might not be at increased risk for monkeypox after exposure.…”
Section: Monkeypox In Persons With Hiv Infectionmentioning
confidence: 99%
“…Prior work has shown that over 60% of persons living with HIV are insured, and among MSM, PrEP users were more frequently insured compared with non-PrEP users 22,23 . Among MSM, gonorrhea incidence has increased for years, particularly among MSM living with HIV and PrEP users 24–26 . Prior work also suggests that one-third of 2020 gonorrhea cases occurred among MSM 27 .…”
Section: Discussionmentioning
confidence: 99%
“…1 A recent report found that gonorrhea diagnoses among men living with diagnosed HIV increased by 61% from 2010 to 2019. 5 Urogenital gonorrhea is more prevalent among MSM with HIV compared with MSM without HIV; no differences were observed in urogenital chlamydia prevalence based on HIV status. 1 Screening programs designed to detect and treat NG/CT are a critical component of the public health response to these infections.…”
mentioning
confidence: 89%
“…Among men, from 2015 to 2019, rates of chlamydia diagnoses increased by 32% and gonorrhea diagnoses increased by 61% 1 . A recent report found that gonorrhea diagnoses among men living with diagnosed HIV increased by 61% from 2010 to 2019 5 . Urogenital gonorrhea is more prevalent among MSM with HIV compared with MSM without HIV; no differences were observed in urogenital chlamydia prevalence based on HIV status 1…”
mentioning
confidence: 99%